VALIDITAS PERANGKAT PEMBELAJARAN INKUIRI BERBASIS KONTEKS DALAM MENINGKATKAN KEMAMPUAN SISWA MEMAHAMI KONSEP CAHAYA - Leny Fryda Noviana; Erman Erman; Wahyu Budi Sabtiawan (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2020)
The research that has been conducted aims to describe the validity of context-based inquiry learning tools in enhancing the ability of students to understand the concept of light The method used in this research is quantitative descriptive method. The research data was obtained from the results of validation conducted by two science lecturers and one junior high school science teacher. In the RPP containing 12 aspects of validity, a score 4 mode was obtained with valid criteria and in the LKS which contained aspects of content, language aspects, presentation aspects and suitability aspects. learning models get a score mode of 5 with very valid criteria. Based on these results, it can be concluded that the validity of the context-based inquiry learning tool is valid in improving students' ability to understand the concept of light.